Morphological Comparison among Striped Puntius (Pisces: Cyprinidae) from Indonesia - HARYONO HARYONO (Society for Indonesian Biodiversity, 2005)
The striped Puntius consisting of four species, these are P. johorensis, P. gemellus, P. trifasciatus, and P. lineatus. This group marked by longitudinal stripe on body, and these varieties. The three species first of them have four long barbells, originally describe by Puntius eugrammus, and the last species has barbells 0-2 (short when present). The strange species was described from Central Mahakam areas, East Kalimantan. Itâ€™s named by Puntius sp., predicted new species but specifically study is needed. This species differ from its congener by the half stripe (+1) above the midlateral stripe on the anterior half of the body.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: striped Puntius, morphology, color pattern, truss morphometric